2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Li, Yi-Feng; Zhu, Xin; Cheng, Zhi-Yang; Liang, Xiao; Zhu, You-Ting; Feng, Dan-Dan; Dobretsov, Sergey; Yang, Jin-Long (Frontiers in Marine Science, 2020)
Bacterial quorum sensing (QS) is a chemical communication that allows bacteria to coordinate their population and gene regulation in response to threshold concentrations of QS signals. Here, we studied the effect of QS inhibitor 2(5H)-furanone (FUR) on the formation of Pseudoaltermonas marina ECSMB14103 biofilms, and the effect of these biofilms on the settlement of plantigrades of the mussel Mytilus coruscus. FUR was added during biofilm formation of P. marina ECSMB14103 or in the settlement bioassay. 10-4M FUR added during biofilm formation significantly (p < 0.05) reduced the settlement of plantigrades, and it was associated with a significant (p < 0.05) reduction of bacterial density. The visualisation of individual substances in biofilms has shown that β-polysaccharides were the major components in the biofilms matrix. The decreased settlement rate may be attributed to the reduction of the biovolume of α-polysaccharides and β-polysaccharides in biofilms. The transcriptome of biofilms treated with 10-4M FUR showed 61 genes were differentially expressed. Aspartate kinase and the flagellar assembly protein fliH gene were significantly affected after exposure to 10-4M FUR (p < 0.05). They are involved in the synthesis of bacterial cell-wall and the mobility of bacteria, respectively. Exposure to 10-4M FUR also significantly changed the carbapenem biosynthesis pathway, which was regulated by QS system in bacteria (p < 0.05). These data suggest that FUR directly affected biofilm formation by altering EPS components and metabolic processes, which in turn indirectly reduced the settlement of plantigrades. The present study provides new insights into molecular mechanisms of controlling biofouling.